2013
DOI: 10.1177/0363546513508763
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Meniscus Allograft Transplantation in Male Professional Soccer Players

Abstract: Arthroscopic MAT in professional soccer players allowed a return to play at the same level (Tegner score of 10) in 75% of the cases at 36-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 27 publications
3
85
2
Order By: Relevance
“…Many studies found significant improvements after MAT in the International Knee Documentation Committee (IKDC) [11,14,15,17,18,20], with percentages between 70 to 90% of nearly normal or normal values [21][22][23]. MAT has provided most patients with pain relief, adequate return to sports, and excellent satisfaction [6][7][8][9]10,11,14,15,17,18,21,[24][25][26][27]. In general, quality of life has even improved after MAT [28], with physical and mental component summary values above those for the matched U.S. population [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies found significant improvements after MAT in the International Knee Documentation Committee (IKDC) [11,14,15,17,18,20], with percentages between 70 to 90% of nearly normal or normal values [21][22][23]. MAT has provided most patients with pain relief, adequate return to sports, and excellent satisfaction [6][7][8][9]10,11,14,15,17,18,21,[24][25][26][27]. In general, quality of life has even improved after MAT [28], with physical and mental component summary values above those for the matched U.S. population [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report a Tegner score in the first 5 years from 3 to 7, corresponding to return to work and recreational sports [7]. Nonetheless, return to high-level competitive sports has been also reported after MAT [24][25][26]. Clinical outcomes like knee effusion, range of motion, stability, or dynamic muscular tests have also improved with MAT [9].…”
Section: Discussionmentioning
confidence: 99%
“…Marcacci et al [24] described the clinical outcomes following MAT in male professional soccer players, with 92 % of patients returning to soccer at an average 11±3 months following surgery. While the authors described significant improvements outcome scores at 1 year, there were no significant improvements at final follow-up 3 years following surgery.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Despite significant improvements in outcome scores at 1 year, these authors found no significant improvements at 3-year follow-up. 9 A second study, however, has shown a 77% return to play in high-level athletes at an average of 17 months, with significant improvements in outcomes at a mean of 3.3 years. 10 The case presented involves this patient population with a 20-year-old collegiate basketball player who foremost wishes to return to sport but also desires to delay progression of degenerative changes.…”
mentioning
confidence: 97%